Probabilidade geométrica: generalizações do problema da agulha de Buffon e aplicações - Silva, Antônio Klinger Guedêlha da (2014)
This paper has the objective of showing Buffon's needle problem, doing a minor generalization of the results obtained hereby, and also presenting some applications based upon the fundamentals of such problem. Buffon's needle problem has been inserted into the study of Theory of Probability, particularly in its sub-area of geometrical probability. In order to attain the solution to this question, in addition to the concepts and the properties concerning the theory of probabilities, it is necessary that one should have some basic knowledge about integral calculus. In chapters 2, 3, and 4 there is a preliminary study of probability, with the basic concepts, properties and formulation of some probabilistic models being presented. During the development of this paper, whenever it was possible, the concepts and definitions were inserted with the aid of a motivational problem and they were solved by means of fixing the same examples as shown. The final chapter presents the importance of Buffon's needle problem as a method of making estimates and as a foundation for the process of capturing images in CT (computerized tomography) scanning machines, such a great breakthrough in what concerns the diagnosis by means of imaging.